Forming an Innovative Start-Up Ecosystem to Increase the Entrepreneurial Activity of Companies (As Exemplified by Asian Countries) - Marat Kamysbayev; Galymzhan Talassov; Arailym Orazgalieva; Serik Nursultanov; Altynbek Moldashev; Gani Kaliev (Qubahan Academic Journal)
This study assesses the development of start-up ecosystems and the effectiveness of government initiatives, determines issues, and proposes measures to support entrepreneurial ecosystems. The aim of the study was to examine how innovative start-up ecosystems contribute to sustainable development and increased entrepreneurial activity in Asian countries, focusing on their strategic importance for economic transformation and technological growth. Using quantitative and qualitative research methods, the authors conduct a comparative analysis of the development of entrepreneurial ecosystems in five Asian countries (Kazakhstan, China, India, South Korea, and Japan) for 2018-2021. The empirical analysis relies on panel data from global databases, applying regression modeling to assess the influence of ecosystem variables on sustainable innovation activity across 20 observations. The data obtained indicates a different degree of development of entrepreneurial ecosystems in the countries under study. Japan and South Korea demonstrate consistently high levels of ecosystem development, while Kazakhstan, China, and India show lower levels but with growth trends. According to the study results, the most influential factors for the development of entrepreneurial activity are state support and policies and access to financing. The findings show that access to financing and state support are the most influential factors in boosting green start-ups and sustainable innovation, with a 1-point increase in funding leading to a 12.6 percentage point rise in eco-innovation activity. To increase entrepreneurial activity, develop open innovations, and achieve SDGs, the authors propose several support measures. These support measures contribute to the formation of start-up infrastructure, including business incubators and accelerators, creating a favorable environment for the development of the venture capital market, building a knowledge exchange system through international cooperation in the framework of open innovation, and holding international hackathons and other events aimed at stimulating innovation and activating knowledge dissemination. Article results offer practical insights for policymakers and ecosystem developers to enhance regulatory frameworks, improve financing mechanisms, and foster global partnerships that support innovation-driven entrepreneurship. Its unique contribution lies in presenting a cross-country, data-driven analysis of entrepreneurial ecosystems in Asia with a focus on sustainability, thereby filling an important gap in the literature on green innovation and start-up policy strategies.